Zein-based nanoparticles: Preparation, characterization, and pharmaceutical application - Liu, Guijin; An, Dongyu; Li, Junjian; Deng, Shiming (Frontiers in Pharmacology, 2023)
Zein, as one of the natural and GRAS proteins in plant, is renewable, nontoxic, biocompatible and biodegradable. Over the past decade, many research efforts have been devoted to zein-based biomaterials for several industrial applications. Combining with research experiences in our research group, the preparation methods, characterizations and pharmaceutical applications of zein-based nanoparticles (zein NPs) were summarized in this review. Zein NPs with different particle nanostructures have been prepared by chemical crosslinking, desolvating, dispersing and micromixing strategies. The pharmaceutical applications of zein NPs are mainly focus on the drug delivery. Zein NPs can improve the drug stability, increase the oral bioavailability, control the drug release and enhance the drug targeting, thereby improving the pharmaceutical effect effectively. More efforts are required to analyze the relationship among preparation methods, particle nanostructures and pharmaceutical properties in virtue of quality by design approach, and further promote the scale-up production and clinical application of zein NPs.